2015
DOI: 10.17222/mit.2014.034
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study and characterization of borided AISI 4140 steel

Abstract: In the present study, an alternative diffusion model was proposed for analyzing the growth of Fe 2 B layers formed on the AISI 4140 steel during the pack-boriding process. This model was based on solving the mass-balance equations for the Fe 2 B/Fe interface to evaluate boron diffusion coefficients through the Fe 2 B layers in a temperature range of 1123-1273 K. The boride incubation time for the Fe 2 B phase was included in the present model. The suggested model was validated experimentally at a temperature o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…They examined the diffusion kinetics of the boron. They determined the boron activation energy as 189.24 kJ•mol -1 in AISI 41240 steel [29]. Dominguez et al borided AISI 4140 steel at temperatures of 850, 900, 950 and 1000 °C for 2, 4, 6 and 8 h. In this study, they found the boron activation energy for the Fe 2 B phase as 173 kJ•mol -1 .…”
Section: Introductionmentioning
confidence: 51%
“…They examined the diffusion kinetics of the boron. They determined the boron activation energy as 189.24 kJ•mol -1 in AISI 41240 steel [29]. Dominguez et al borided AISI 4140 steel at temperatures of 850, 900, 950 and 1000 °C for 2, 4, 6 and 8 h. In this study, they found the boron activation energy for the Fe 2 B phase as 173 kJ•mol -1 .…”
Section: Introductionmentioning
confidence: 51%
“…Figure 1(a) shows the microstructural images of AISI 4140 steel boronized at 900 °C for 4 hours. When the boronizing layers are examined, a structure with porous but having a columnar morphology is encountered as in the literature [27]. Since the outermost surface of the coating is damaged due to the polishing process, it seems to be porous.…”
Section: Characterization Of Boride Layersmentioning
confidence: 99%
“…By applying the boundary condition on the surface, Eq. (13) was obtained: (13) Taking into account the boundary condition at the (FeB/Fe 2 B) interface, Equation ( 14) was deduced as follows: (14) By integrating the second Fick's law between 0 and u(t) for the FeB phase and from u(t) to v(t) for the Fe 2 B phase and applying the Leibniz rule (see Appendix for more details), the two ordinary differential Eqs. (15) and (16) were obtained :…”
mentioning
confidence: 99%